Monomeric state of S100P protein: Experimental and molecular dynamics study. (June 2019) - Permyakov, Sergei E.; Denesyuk, Alexander I.; Denessiouk, Konstantin A.; Permyakova, Maria E.; Kazakov, Alixey S.; Ismailov, Ramis G.; Rastrygina, Victoria A.; Sokolov, Andrei S.; Permyakov, Eugene A.
Graphical abstract: Highlights: The transition from the dimeric to monomeric form of S100 P results in a decrease in protein thermal stability. IL-11 has only one S100P-binding site and the interaction of monomeric S100P with IL-11 differs from that for oligomeric form. The separated S100P monomer can have a compact globular structure. Abstract: S100 proteins constitute a large subfamily of the EF-hand superfamily of calcium binding proteins. They possess one classical EF-hand Ca 2+ -binding domain and an atypical EF-hand domain. Most of the S100 proteins form stable symmetric homodimers. An analysis of literature data on S100 proteins showed that their physiological concentrations could be much lower than dissociation constants of their dimeric forms. It means that just monomeric forms of these proteins are important for their functioning. In the present work, thermal denaturation of apo-S100P protein monitored by intrinsic tyrosine fluorescence has been studied at various protein concentrations within the region from 0.04–10 μM. A transition from the dimeric to monomeric form results in a decrease in protein thermal stability shifting the mid-transition temperature from 85 to 75 °C. Monomeric S100P immobilized on the surface of a sensor chip of a surface plasmon resonance instrument forms calcium dependent 1 to 1 complexes with human interleukin-11 (equilibrium dissociation constant 1.2 nM). In contrast, immobilized interleukin-11 binds two molecules of dimeric S100P with dissociation constants of 32 nM and 288 nM. Since effective dissociation constant of dimeric S100P protein is very low (0.5 μM as evaluated from our data) the sensitivity of the existing physical methods does not allow carrying out a detailed study of S100P monomer properties. For this reason, we have used molecular dynamics methods to evaluate structural changes in S100P upon its transition from the dimeric to monomeric state. 80-ns molecular dynamics simulations of kinetics of formation of S100P, S100B and S100A11 monomers from the corresponding dimers have been carried out. It was found that during the transition from the homo-dimer to monomer form, the three S100 monomer structures undergo the following changes: (1) the helices in the four-helix bundles within each monomer rotate in order to shield the exposed non-polar residues; (2) almost all lost contacts at the dimer interface are substituted with equivalent and newly formed interactions inside each monomer, and new stabilizing interactions are formed; and (3) all monomers recreate functional hydrophobic cores. The results of the present study show that both dimeric and monomeric forms of S100 proteins can be functional.